Safety and effectiveness of a novel generator algorithm for bipolar vessel sealing: a randomised controlled chronic animal study - Kraemer, Bernhard; Tsaousidis, Christos; Kruck, Stephan; Schenk, Martin; Scharpf, Marcus; Kommoss, Stefan; Brucker, Sara; Nuessle, Daniela; Enderle, Markus D.; Biber, Ulrich (BMC surgery, 2019)
Background Electrosurgical vessel sealers are gradually replacing conventional techniques such as ligation and clipping. Algorithms that control electrosurgical units (ESU), known as modes, are important for applications in different surgical disciplines. This chronic porcine animal study aimed to evaluate the safety and effectiveness of the novel thermoSEAL electrosurgical vessel sealing mode (TSM). The BiClamp® mode (BCM) of the renowned VIO® 300 D ESU served as control. BCM has been widely available since 2002 and has since been successfully used in many surgical disciplines. The TSM, for the novel VIO® 3 ESU, was developed to reduce sealing time and/or thermal lateral spread adjacent to the seal while maintaining clinical success rates. The primary aim of this study was to investigate the long-term and intraoperative seal quality of TSM. Methods The BiCision® device was used for vessel sealing with TSM and BCM in ten German Landrace pigs which underwent splenectomy and unilateral nephrectomy during the first intervention of the study. The seals were cut with the BiCision® knife. Ninety-nine arteries, veins and vascular bundles were chronically sealed for 5 or 21 days. Thereafter, during the second and terminal intervention of the study, 97 additional arteries and veins were sealed. The carotid arteries were used for histological evaluation of thermal spread. Results After each survival period, no long-term complications occurred with either mode. The intraoperative seal failure rates, i.e. vessel leaking or residual blood flow after the first sealing activation, were 2% with TSM versus 6% with BCM ( p = 0.28). The sealing time was significantly shorter with TSM (3.5 ± 0.69 s vs. 7.3 ± 1.3 s, p < 0.0001). The thermal spread and burst pressure of arteries sealed with both modes were similar ( p = 0.18 and p = 0.61) and corresponded to the histological evaluation. The measured tissue sticking parameter was rare with both modes ( p = 0.33). Tissue charring did not occur. Regarding the cut quality, 97% of the seals were severed in the first and 3% in the second attempt (both with TSM and BCM). Conclusions The novel TSM seals blood vessels twice as fast as the BCM while maintaining excellent tissue effect and clinical success rates. Trial registration Not applicable.